The Nordic Gene Bank’s Prunus clone archive in Finland: II Local races of plum - Palonen, Pauliina; Uosukainen, Marjatta; Laurinen, Eeva (Agricultural and Food Science, 1998)
The morphological variation in 104 local races of plum (Prunus domestica subsp. domestica L.) in the Nordic Gene Bank’s Prunus clone archive in Pälkäne, Southwest Finland was examined. Each tree was described using 37 characteristics. On the basis of fruit characteristics the local races were classified into three main groups. The largest one was the red plum group, the yellow plum group being the second largest. Victoria-type plums, which have not been reported to occur in Finland before and which resemble the English cultivar ‘Victoria’, make up the third group. Victoria-type plums proved to be fully and red plums partly self-compatible, whilst the yellow plums were selfincompatible. All the local races of plum were evaluated for their possible further use. Two of them were selected for commercial propagation.